EFFICIENCY OF DIFFERENT TRAP TYPES FOR ATTRACTING TOMATO LEAF MOTH Tuta absoluta UNDER FIELD CONDITIONS - Mohammed Mirza; Shamal Al-Mufti (Mesopotamia Journal of Agriculture)
Field studies were conducted in the Sharya-Duhok / Kurdistan Region of Iraq to evaluate the influence of different light colors, three installation heights, and three types of traps on the capture of the tomato leaf miner moth. The light colors tested were yellow, white, green, blue and red. The trap installation heights were 70, 100, and 130 cm above ground level. The traps included a delta trap, a water trap and a new combined pheromone-equipped sticky light trap, referred to as the GLT trap. Results indicated that the white light was significantly more attractive to the tomato leaf miner, capturing 32% of the total moths, followed by the yellow, blue, green and red light with percentages (27, 22, 13, 6%), respectively. This significantly differed from traps installed at heights of 70 cm captured 70% of the total number caught, and it differed statistically from the traps installed at a height of 100 and 130 cm, which captured 19 and 11%, respectively, this suggests that moth flight activity is concentrated at the plant canopy level. The GLT trap demonstrated remarkable superiority over other trap types, capturing 52% of the total moths, significantly differing from the delta and water traps, which captured 37% and 11%, respectively. This suggests that exploiting the pest's behaviors, such as using the GLT trap, could be a promising approach to managing the pest in infested fields within a short period, complementing chemical control methods.